Medical ozone arrests oxidative damage progression and regulates vasoactive mediator levels in elderly patients (60–70 years) with oxidative etiology diseases - León Fernández, Olga Sonia; Oru, Gabriel Takon; Viebahn-Hänsler, Renate; López Cabreja, Gilberto; Serrano Espinosa, Irainis; García Fernández, Elizabeth (Frontiers in Physiology, 2022)
Medical ozone reestablishes cellular redox balance so that it may be a valid therapeutic approach in the prevention and management of age-related diseases with oxidative etiology in older people. The aim of this study is to evaluate oxidative stress and some vasoactive substances in older (60-70 years) rheumatoid arthritis (AR) patients with diabetes and hypertension as well as another group subject with bronchial asthma in order to demonstrate the beneficial effects of medical ozone in the prevention and therapy of these age groups. A randomized clinical study with 45 older patients (60-70 years) was performed. Group I (n = 15) RA + diabetes and hypertension receiving no ozone treatment, and Group II (n = 30) treated with medical ozone. This group was divided into two subgroups (n = 15 each), Group IIa: the same as group I + medical ozone and Group IIb: bronchial asthma patients. Indicators of RA in I and IIa groups were evaluated. Redox balance was assessed through defense and injury biomarkers. Thromboxane A2 (TXA2) and Prostacyclin levels were assessed in Group IIb patients. Medical ozone arrested oxidative injury progression in Ia group and decreased thromboxane levels as well as TXA2/6 keto PGF1α ratio in IIb group. Medical ozone arrested the progression of oxidative damage and modulated those endogenous mechanisms that promote a suitable redox status and TXA2/PGI2 balance. These results suggest that medical ozone may become a standard approach in the prevention and management of age-related oxidative diseases on elderly people.